Correlation between Estimated Fetal Weight at Term by Ultrasonogram and Actual Birth Weight - Shapla, NR; Aleem, MA; Jesmin, E; Ahmed, H; Lepe, YS (Journal of Bangladesh College of Physicians and Surgeons, 2014)
The estimation of foetal birth weight is an important factor in the management of high risk pregnancies. Estimated foetal weight is calculated in the standard routine antepartum evaluation of high risk pregnancies and deliveries. This prospective observational study was done at the Department of Obstetrics and Gynecology in Border Guard Hospital, Peelkhana, Dhaka over a period of 6 months from January 2012 to June 2012. The present study was carried out to compare the accuracy of actual and ultrasonographic estimation of foetal weight at term. Hundred pregnant women at different gestational age from 37 weeks to 40 weeks were selected by simple random sampling. Ultrasonography was done for determination of estimated foetal weight (EFW) at term by using Hadlock method and birth weight was measured just after delivery. Data analysis was done by percentage and paired t test. The age range of patients were 18-37 years with mean ±SD is 25.13±4.46. Among 100 study patients 33% were nuliparous and 67% were multiparous. The mean ±SD of gestational age and actual birth weight is 38.76±1.09 and 3.11±0.391 respectively. Ultrasound biometric data that includes mean ±SD biparietal diameter (BPD) in mm, abdominal circumference (AC) in mm and femur length (FL) in cm were 90.21±3.52, 327.67±20.75 and 7.45±1.43 respectively. Mean ±SD of estimated foetal weight (EFW) Kg was 2.97±0.53. Actual birth weight is correlated with the estimated foetal weight and the result was not statistically significant (P >.05). Calculation of estimated fetal weight by ultrasonography is recommended to make decision about mode of delivery, so that an obstetrician can plan early in high risk cases. DOI: http://dx.doi.org/10.3329/jbcps.v32i1.21032 J Bangladesh Coll Phys Surg 2014; 32: 21-25